Vozes amazônidas: a experiência de democratização da comunicação da rede de notícias da Amazônia - Reinheimer, Joseani (2022)
Democratization of Communication is a topic under constant discussion, since in Brazil large communication companies own more than one television station and more than one radio station. The Amazon News Network was created in 2008 with the objective of giving space for the social struggles to echo their voices, and currently has 20 associated stations located in seven states within the Legal Amazon. It produces two radio programs, a newspaper and a radio magazine. Among RNA's objectives are to democratize communication, respecting the environment and valuing the people and the local culture. This paper aims to analyze how this process of democratization of communication happens and how it reflects in the programs produced by RNA.